Police Officers’ Presumption of Innocence: History, Contemporaneousness and Possibility to Implement into Ukrainian Legislation - V. V. Sokurenko (Bulletin of Kharkiv National University of Internal Affairs)
The article is focused on the analysis of the legal category of police officers’ presumption of innocence. Accordingly, the purpose of the research is to provide comprehensive characteristics of police officers’ presumption of innocence, taking into account international practice of its formation and development. To achieve this purpose, the author has formulated the following tasks: 1) study of the historical aspect of the origin and formation of police officers’ presumption of innocence, including within the qualification immunity of police officers; 2) analysis of the practice of applying qualification immunity in the United States of America; 3) objective reveal of the content and essence of police officers’ presumption of innocence; 4) outlining the possibilities of introducing the police officers’ presumption of innocence into the legislation of Ukraine.